2009
DOI: 10.1038/bmt.2009.38
|View full text |Cite
|
Sign up to set email alerts
|

Drug interaction between voriconazole and calcineurin inhibitors in allogeneic hematopoietic stem cell transplant recipients

Abstract: Although voriconazole has been shown to interact with calcineurin inhibitors, this interaction has not been thoroughly examined. The purpose of this study was to evaluate the drug interaction between voriconazole and calcineurin inhibitors among recipients of allogeneic hematopoietic stem cell transplantation (HSCT). Twenty-one recipients of allogeneic HSCT were evaluated. Those recipients had been on CsA (n ¼ 10) or tacrolimus (n ¼ 11) when voriconazole (400 mg per day orally, or 8 mg/kg per day, i.v.) was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 13 publications
1
55
2
Order By: Relevance
“…In that study, measurement of baseline tacrolimus concentrations, followed by serial drug blood concentrations after the addition of voriconazole resulted in median tacrolimus blood concentrations, that is, 115% (25-308%) above the target range. 21 This study shows the large interpatient variability of the interaction and demonstrates the need for continued monitoring. It is important to note that a preemptive dose-reduction strategy was not used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, measurement of baseline tacrolimus concentrations, followed by serial drug blood concentrations after the addition of voriconazole resulted in median tacrolimus blood concentrations, that is, 115% (25-308%) above the target range. 21 This study shows the large interpatient variability of the interaction and demonstrates the need for continued monitoring. It is important to note that a preemptive dose-reduction strategy was not used in their study.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to other azole antifungal agents, not only oral but also intravenous administration of ITCZ significantly affected the blood concentration of CsA. [20][21][22] Concerning the interaction between VRCZ and CsA, Mori et al 23 reported that the administration of VRCZ to patients receiving CsA resulted in a significant increase in the concentration/dose ratio of CsA, but the route of VRCZ administration did not affect the changes in the concentration/dose ratio. If we consider these findings together, it may be reasonable to suggest that the interaction between azole antifungal agents and CsA is stronger when the antifungals are given orally, but the difference becomes unclear with ITCZ and VRCZ, as the interactions of these agents are stronger than that of FLCZ and can be detected even when they are given intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies describing a clinically significant drug interaction with calcineurin inhibitors in renal transplants and HSCT recipients. [18][19][20] In order to reduce the impact of other drug interactions, our study compared the initial concentration of calcineurin inhibitor, because at that time the patients were uniformly administered omeprazole, itraconazole, ciprofloxacin and acyclovir. In our study, the conditioning regimen also did not affect the initial concentration of the calcineurin inhibitor.…”
Section: Discussionmentioning
confidence: 99%